Application of informatics in cancer research and clinical practice: Opportunities and challenges. Issue 1 (15th June 2022) - Hong, Na; Sun, Gang; Zuo, Xiuran; Chen, Meng; Liu, Li; Wang, Jiani; Feng, Xiaobin; Shi, Wenzhao; Gong, Mengchun; Ma, Pengcheng
Abstract: Cancer informatics has significantly progressed in the big data era. We summarize the application of informatics approaches to the cancer domain from both the informatics perspective (e.g., data management and data science) and the clinical perspective (e.g., cancer screening, risk assessment, diagnosis, treatment, and prognosis). We discuss various informatics methods and tools that are widely applied in cancer research and practices, such as cancer databases, data standards, terminologies, high‐throughput omics data mining, machine‐learning algorithms, artificial intelligence imaging, and intelligent radiation. We also address the informatics challenges within the cancer field that pursue better treatment decisions and patient outcomes, and focus on how informatics can provide opportunities for cancer research and practices. Finally, we conclude that the interdisciplinary nature of cancer informatics and collaborations are major drivers for future research and applications in clinical practices. It is hoped that this review is instrumental for cancer researchers and clinicians with its informatics‐specific insights. Abstract : This review summarized the progress of cancer informatics in the big data era. Various informatics methods and tools that are widely applied in cancer research and practices were discussed. This review further addressed the informatics challenges and opportunities for the comprehensive cancer field. It is expected that this review is instrumental for cancer researchers and clinicians with an informatics‐specific insight.